The Effectivity of Repetitive Transcranial Magnetic Stimulation on Motor Function of Acute Ischemic Stroke Patients in Dr. Mohammad Hoesin General Hospital Palembang - Anggraeni, Dya; Muhammad Hasnawi Haddani; Achmad Junaidi; Pinto D Ramadhoni; Asep Riswandi (Jurnal RSMH Palembang, 2023)
Background: More than 60% of stroke patients suffered from long-term disability due to motor impairment despite underwent intensive rehabilitative therapies. Non-invasive brain stimulation such as repetitive Transcranial Magnetic Stimulation (rTMS) has been reported in improving motor function after stroke through the mechanism of neuroplasticity. Research related to the use of rTMS as adjunctive therapy in ischemic stroke cases has mostly been carried out in chronic stroke patients and until now only a few studies have assessed the effectivity of rTMS in patients with acute stroke. Therefore, this study aims to assess whether rTMS can improve motor function in patients with acute ischemic stroke. Methods: This research was a randomized controlled trial and carried out acute ischemic stroke patients in Dr. Mohammad Hoesin Hospital Palembang. A total of 22 patients were randomly divided into a control group with standard therapy (11 subjects) and a treatment group with standard therapy and 5 sessions of rTMS (11 subjects). Improvement of motor function was assessed with motor strength using the Medical Research Council (MRC) scale performed before and after the intervention on the four limb segments. Bivariate analysis with Paired T-Test was used to compare the strength before and after the intervention in each group and the Mann Whitney Test used to compare the differences of motor strength between groups. Results: All subjects in both groups completed the study and no adverse effects were found in the rTMS group. The MRC scale after the intervention increased in all segments in both groups, but significant differences were only found in the treatment group (hand grip (p=0.011), shoulder abduction (p=0.001), hip flexion (p=0.001), and toe dorsiflexion (p =0.002)). Comparison of differences in motor strength between the two groups using the Mann Whitney Test revealed that the improvement was more significant in the rTMS group compared to the control group (p=0.024, p=0.031, p=0.016, and p=0.021). The motor strength in the rTMS group start to increase on the second and third day and particularly reached the peak on the fourth day after the procedure. Multivariate analysis showed no effect of confounding factors such as age, sex, BMI, comorbidities, onset, lesion location, NIHSS, and mRS inthe improvement of motor strength. Conclusion: rTMS therapy can improve motor function in acute ischemic stroke patients and can be considered as an adjuvant therapy in assisting the recovery of post-stroke motor impairment.